(untitled) (KYAMC Journal, 2018)
Background : Self poisoning with organophosphate pesticides is a major health problem in world wide. Organophosphorus compound poisoning is a very common toxicological emergency encountered at Mirzapur in Tangail. It is particularly common among the rural agricultural worker’s which comprise a substantial group of the population of this region. Objective: The objective of this study was to find out the incidence, frequency, pattern of poisoning, outcome and aetiological aspect of Organo phosphorus poisoning patient admitted in Kumudini Women’s Medical college Hospital. Methods: A total 366 cases of OPC poisoning were analysed during 1 year from January 2015 to December 2015. The emphasis was given on age, sex, socio-economic status, occupation, motive of poisoning, types of compound consumed its quality, place, distance from referral place and the ultimate outcome. Results: Young population of rural background, particularly agricultural workers were the commonest patients (51.91%). The most common motive of poisoning was with a suicidal intent, both in males (27.59%) and females (66.39%). Financial crisis was one of the most common reasons analysed as the motive behind the poisoning (54.20%). Three hundred forty four Patients recovered and 22 were expired. The major cause of death in these cases was respiratory failure followed by multi-organ failure. Conclusion : Strict of the pesticide act and involving a new policy by the government to educate the public and youth in large about the dangerous, life threatening effects of Organophosphorus compound could help amelerioating the harmful effects of such poisoning. KYAMC Journal Vol. 9, No.-3, October 2018, Page 133-135